2007
DOI: 10.1161/01.str.0000259853.43084.03
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Alterations in Functional and Pharmacological Arteriolar Reactivity After Subarachnoid Hemorrhage

Abstract: Background and Purpose-Disturbances in cerebral arteriolar function, in addition to large vessel vasospasm, may be responsible for ischemia after subarachnoid hemorrhage. The purpose of this study was to test the hypothesis that subarachnoid hemorrhage alters cerebral microvascular reactivity. Methods-An endovascular filament model was used to induce subarachnoid hemorrhage in halothane-anesthetized male Sprague-Dawley rats. We evaluated pial arteriolar responses to sciatic nerve stimulation, topically applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
2
20
1
Order By: Relevance
“…In contrast to our findings, Britz et al obtained conflicting results using CO 2 , adenosine, and sodium nitroprusside (SNP) in an endovascular filament model of SAH in rats (Britz et al, 2007). They found that CO 2 reactivity was unaffected by SAH.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, Britz et al obtained conflicting results using CO 2 , adenosine, and sodium nitroprusside (SNP) in an endovascular filament model of SAH in rats (Britz et al, 2007). They found that CO 2 reactivity was unaffected by SAH.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results demonstrated that SAH impaired the pial dilating response to common vascular dilating stimuli, such as SNS, CO 2 , ACh, and ADO, which is consistent with previous reports [16,20,21]. However, inhibition of HMGB1 by its antagonist or receptor-binding inhibitors did not change the response, suggesting that HMGB1 might not play a significant role in pial vessel reactivity during SAH, at least in our rat model of SAH.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence obtained in rodents (Britz et al, 2007;Jorks et al, 2011;Koide et al, 2012) suggested that vasodilatory impairments following SAH could arise in arterioles, and may be linked to the elevated presence of inflammatory factors (Kolias et al, 2009;Pradilla et al, 2010). Findings from our laboratory, in rats subjected to transient focal ischemia (Watcharotayangul et al, 2012) or transient forebrain ischemia (TFI), (Xu et al, 2006) suggested a direct correlation between post-ischemic pial venular leukocyte activity and brain damage.…”
Section: Introductionmentioning
confidence: 73%